A magnetic fluorescence molecularly imprinted polymer sensor with selectivity for dibutyl phthalate via Mn doped ZnS quantum dots. Issue 81 (6th November 2017) - Xu, Wanzhen; Li, Tao; Huang, Weihong; Luan, Yu; Yang, Yanfei; Li, Songjun; Yang, Wenming
Abstract : In this work, magnetic quantum dots molecularly imprinted polymers were synthesized, which were based on ZnS and magnetic Fe3 O4 . Abstract : In this work, magnetic quantum dots molecularly imprinted polymers were synthesized, which were based on ZnS and magnetic Fe3 O4 . The polymers had a spherical shape and a core–shell structure and exhibited a magnetic strength of 17.20 emu g −1 and optical stability. After the experimental conditions were optimized, the fluorescence intensity showed a linear dependence with concentration from 5.0 μmol L −1 to 50 μmol L −1, with R 2 = 0.9960. Upon optimizing the experimental conditions, the linear dependence of fluorescence intensity with concentration ranged from 5.0 μmol L −1 to 50 μmol L −1, with a detection limit of 0.08 μmol L −1 . Furthermore, the MQDs–MIPs were successfully used for the detection of a tap water sample. With three spiking concentration levels, the recovery rate of each experiment was from 99.45 to 103.4%, with a relative standard deviation from 1.97 to 3.37%. This study provides a promising strategy for fabricating magnetic fluorescence molecular imprinted polymers with highly selective recognition ability.